Access to Minimally Invasive Gynecologic Surgery for Adnexal Surgery: Impact of Race and Payer Mix [03H]. (May 2020) - Palvia, Vijay; Finkelstein, Mark; Zakashansky, Konstantin; Brodman, Michael; Ascher-Walsh, Charles; Khalil, Susan
Abstract : INTRODUCTION: Minimally invasive gynecologic surgery is associated with many benefits. Adoption for hysterectomy, has noticeable variation with race. The Statewide Planning and Research Cooperative System (SPARCS) is a comprehensive all payer data reporting system, the result of cooperation between healthcare industry and government including outpatient and inpatient information on procedures, diagnosis, and patient factors. METHODS: The (SPARCS) database was reviewed from 2011–2015, for ovarian-cystectomy with/without salpingectomy for benign indications, performed via laparotomy and laparoscopy. RESULTS: There were 68, 029 patients included in this analysis. Average age was 43 years, with 81.3% between 18–55, 17.7% >55. Racial composition comprised of 68.7% Caucasian, 4.8% Asian, 11.2% Black, and 15.3% as other. Payor mix included 79.6% insured, 7.4% Medicaid, 8.3% Medicare, and 4.7% other or self-payment. Majority resided in metropolitan areas (90.6%), and did not travel >15 miles for care. Of the 68, 029 that were included, 54, 829 were performed via laparoscopy while 13, 200 were via laparotomy. Odds ratio (OR) of having procedure via laparoscopy was 0.68 for black, 0.81 for Hispanic, and 0.80 for other. Compared to insured: OR that surgery was via laparoscopy was 0.69 for Medicaid, 0.72 for Medicare, 0.92 self. At high-volume surgical facilities the OR laparoscopy was utilized was 1.83 compared to a low volume facility, and 1.49 at medium volume facilities. At institutions with major teaching affiliation the OR was 0.91 compared to non-teaching, and the OR was 1 for minor affiliation. CONCLUSION: Race is not the only factor associated with lower likelihood of laparoscopy, other factors such as institution type also impact likelihood.